2017
DOI: 10.1055/s-0043-109434
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Biological Effects of Hydroalcoholic Extract of Hibiscus Rosa Sinensis Flowers on Alloxan Induced Diabetes in Rats

Abstract: The current study sought to investigate antidiabetic, hypolipidimic, antioxidant and histopathological effects of floral extract of Hibiscus rosa sinensis in Alloxan induced Diabetes in rats. Study was conducted on 6 groups with 6 wistar rats in each group for the period of 4 weeks. Group I: served as normal control (NC), rats administered with gum acacia 1 ml daily, group II: consider as diabetic control (DC) treated with alloxon 150 mg/kg body wt. Whereas Hibiscus rosa-sinensis flower extract was given orall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Flower extract of HRS was more efficacious in lipid lowering effect and in antioxidative activity than glibenclamide. After 28 day treatment with flower extract, size of islets was significantly increased and necrosis and atrophy of islets were significantly improved; also increase in number and diameter of cell islets compared to the diabetic group (151) . Blood glucose and total lipid levels were determined in Streptozotocin induced diabetic rats after oral administration of an ethanol flower extract of Hibiscus rosa sinensis.…”
Section: Hibiscus Rosa Sinensismentioning
confidence: 88%
“…Flower extract of HRS was more efficacious in lipid lowering effect and in antioxidative activity than glibenclamide. After 28 day treatment with flower extract, size of islets was significantly increased and necrosis and atrophy of islets were significantly improved; also increase in number and diameter of cell islets compared to the diabetic group (151) . Blood glucose and total lipid levels were determined in Streptozotocin induced diabetic rats after oral administration of an ethanol flower extract of Hibiscus rosa sinensis.…”
Section: Hibiscus Rosa Sinensismentioning
confidence: 88%
“…Fertility regulation, which includes contraception and infertility management, is an essential component of reproductive health [24][25][26]. The effect of antiandrogens on the reproductive system and fertility of male albino rats was described by Al-Hady [24].…”
Section: Discussionmentioning
confidence: 99%
“…Further, significant anti-diabetic effects which were comparable to glibenclamide and sulphonylurea were observed with the same dosed administered for 28 days. Histopathological studies showed an increase in the size and number of islets, diameter of the islet cells and decrease in the necrosis and atrophy of the islets (Pethe et al, 2017). After administrating ethanolic Hibiscus flower extract for 21 days, a maximum blood glucose lowering of 41-46% and total cholesterol and serum triglycerides lowering of 22 and 30%, respectively were observed with Streptozotocine induced diabetic rats.…”
Section: Antihypercholesterolemic Effectsmentioning
confidence: 93%